Manajemen dan Tata Kelola Perpustakaan Perguruan Tinggi Berbasis Student-Centered Governance - Wicaksono, Moch. Fikriansyah (Universitas Syiah Kuala, 2025)
This article examines how library management and governance can be strengthened in higher education institutions through the systematic adoption of international standards and national regulations. The study addresses the problem of fragmented governance practices, unclear accountability, and uneven performance measurement that limit service quality and user engagement. Data were collected through an integrative review of authoritative standards and frameworks, complemented by documentary analysis of Indonesian regulations for academic libraries. The analysis employed a thematic synthesis and framework analysis to map findings onto core governance dimensions: strategic direction, organizational structure, decision-making processes, accountability and transparency, performance indicators, impact assessment, and stakeholder participation. The results articulate a practical governance model that aligns management processes with performance and impact measurement, clarifies roles and responsibilities, and embeds student participation in policy and service design. The model specifies measurable performance indicators, recommends procedures for assessing library impact on learning and research, and identifies common implementation challenges, including resource constraints and resistance to change, alongside feasible mitigation strategies. The study concludes that a standards-aligned governance architecture improves accountability, evidences value, and supports continuous improvement. It offers actionable guidance for library leaders to integrate management routines with governance mechanisms and to institutionalize evidence-based decision making in academic libraries.